Age-related decreased inhibitory vs. excitatory gene expression in the adult autistic brain - van de Lagemaat, Louie N.; Nijhof, Bonnie; Bosch, Daniëlle G. M.; Kohansal-Nodehi, Mahdokht; Keerthikumar, Shivakumar; Heimel, J. Alexander (Frontiers in Neuroscience, 2014)
Autism spectrum disorders (ASDs) are neurodevelopmental disorders characterised by impaired social interaction and communication, and restricted behaviour and interests. A disruption in the balance of excitatory and inhibitory neurotransmission has been hypothesised to underlie these disorders. Here we demonstrate that genes of both pathways are affected by ASD, and that gene expression of inhibitory and excitatory genes is altered in the cerebral cortex of adult but not younger autistic individuals. We have developed a measure for the difference in the level of excitation and inhibition based on gene expression and observe that in this measure inhibition is decreased relative to excitation in adult ASD compared to control. This difference was undetectable in young autistic brains. Given that many psychiatric features of autism are already present at an early age, this suggests that the observed imbalance in gene expression is an ageing phenomenon in ASD rather than its underlying cause.